Art & creative development for young children - Fox, Jill Englebright (Wadsworth Cengage Learning, 2012)
A resource for establishing and implementing a developmentally appropriate art program. Written for pre-service and in-service early childhood professionals in child care, preschool, or kindergarten through third grade settings, it takes a child-centered approach to art education. It blends theory and research with practical applications.